Attentional focus and children: Do childhood characteristics or expertise mediate the effects on motor learning? - Francisco Milton Gonçalves Pereira Júnior; Giordano Marcio Gatinho Bonuzzi (Asociación Española de Ciencias del Deporte, 2022)
In adults, longitudinal external focus benefits the motor performance of high-skilled performers. While low-skilled performers benefit from a proximal external focus. Children seem to respond differently to adults regarding the effects of attentional focus on motor learning, and the cause of this difference remains unclear. The present study investigated the effects of the attentional focus distance on motor performance and learning of high-skilled children. Forty-five 8-years-old high-skilled children were divided into three groups with different attentional focus distances (internal, proximal external and distal external). All participants practiced an inside-of-the-foot kick soccer task in 5 blocks of 10 trials. Motor performance was assessed through absolute and variable errors before the practice (pre-test), immediately after the practice (post-test), and after 24-hours (retention test). As inferential analyses, we run an ANOVA two-way (3 groups x 3 times) for absolute and variable errors. For absolute error, there was an effect in time (p < .0001), with improvement across practice and retention; also, the distal external group demonstrated lower absolute error than other groups (p < .0001). In contrast, proximal external focus provides a lower variability inter-trials (but with a lower score) (p < .001). Our findings suggested that distal external attentional focus benefits motor performance and learning of skilled children. Practice and experience are the predominant factors in this interaction, as it happens in adults. Childhood characteristics seem not to influence this process.